Vegetation Structure and Species Composition Along a Canal-Distance Gradient Across Different Peatland Land Use Types - Silviana, Sinta Haryati; Saharjo, Bambang H.; Sutikno, Sigit; Vetrita, Yenni (HAYATI Journal of Biosciences, 2026)
Tropical peatlands are critical ecosystems that provide habitat for biodiversity and store large amounts of carbon, yet they are increasingly degraded due to land-use conversion, drainage, and recurrent fires. This study examined vegetation structure and species composition along a canal-distance gradient (10-350 m across three peatland land-use types: rubber plantation, secondary forest, and burned peatland. Vegetation surveys were conducted using 40 nested plots covering four growth strata (trees, poles, saplings/shrubs, and seedlings/herbs). Community structure was analyzed using the Importance Value Index (IVI), Shannon–Wiener diversity index (H′), Margalef’s richness index (DMg), Pielou’s evenness index (E), and Simpson’s dominance index (C). Differences in environmental parameters among land-use types were tested using one-way ANOVA (p